Responsivitas Pegawai Kantor Unit Penyelenggara Pelabuhan Kelas III Larea-Rea Di Kabupaten Sinjai - Hidayat, Mardhatillah; Mappamiring, Mappamiring; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine how the ability to respond, speed of services, accuracy of serving, accuracy of serving, punctuality of serving and the ability to respond to camplaints at the Larea-rea Class III Port Administration Unit Office In Sinjai Regency. This study used descriptive qualitative research. The number of informants were 12 people. Data collection techniques were observation, interviews, and documentation. The results of this study showed that how the service delivery process was measured using indicators consisting of responsiveness, speed of service, accuracy of serving, punctuality of service was good. However, in appropriate service indicators, it was necessary to disseminate information so that service users know what was the procedure of the office, and the ability to complaints was still low due to the unavailability of suggestion boxes and inadequate toilet facilities. Keywords:responsiveness, public services, port services